A rare case of a gigantic myxoid liposarcoma of vulva: case report - Kaur, Tanudeep; Singh, Ravinder P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Vulval malignancies per se are very rare and a liposarcoma in this location is rarer still. The literature consists only of case reports of patients, often with a very limited follow up. We present a rare case of a young 30 year old unmarried nulliparous woman presenting with a giant vulval mass of 30×20 cm and weighing nearly 6 kilograms. Ultrasonography, Computed Tomography, Magnetic Resonance Imaging and biopsy were done. Local resection with adjuvant radiotherapy was given. Histopathology was suggestive of myxoid liposarcoma and the patient is presently recurrence free with over 8 years of follow up. Though rare, myxoid liposarcoma should be kept in differential diagnosis of vulval soft tissue mass. Management includes a combination of surgery and radiation. Excision of lymph nodes is not recommended. Strict prolonged follow up for recurrence or metastasis is mandatory, and any new complaints should be addressed promptly. This is particularly true in the setting of liposarcoma, which may exhibit unusual patterns of spread and recurrence.